Sorbent materials for rapid remediation of wash water during radiological event relief. (November 2016) - Jolin, William C.; Kaminski, Michael
Abstract: Procedures for removing harmful radiation from interior and exterior surfaces of homes and businesses after a nuclear or radiological disaster may generate large volumes of radiologically contaminated waste water. Rather than releasing this waste water to potentially contaminate surrounding areas, it is preferable to treat it onsite. Retention barrels are a viable option because of their simplicity in preparation and availability of possible sorbent materials. This study investigated the use of aluminosilicate clay minerals as sorbent materials to retain 137 Cs, 85 Sr, and 152 Eu. Vermiculite strongly retained 137 Cs, though other radionuclides displayed diminished affinity for the surface. Montmorillonite exhibited increased affinity to sorb 85 Sr and 152 Eu in the presence of higher concentrations of 137 Cs. To simulate flow within retention barrels, vermiculite was mixed with sand and used in small-scale column experiments. The GoldSim contaminate fate module was used to model breakthrough and assess the feasibility of using clay minerals as sorbent materials in retention barrels. The modeled radionuclide breakthrough profiles suggest that vermiculite-sand and montmorillonite-sand filled barrels could be used for treatment of contaminated water generated from field operations. Graphical abstract: Highlights: Vermiculite and montmorillonite are proposed for use in retention barrels. Retention barrels retain radionuclides while allowing for wash water flow. Vermiculite demonstrated a high selectivity for 137 Cs. Montmorillonite displayed the ability to sorb low concentrations of 85 Sr.